STUDI SOSIAL EKONOMI TRANSMIGRAN DI NAGARI LUNANG KECAMATAN LUNANG KABUPATEN PESISIR SELATAN - Putri, Siska Desnila; Juita, Erna; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
This study aimed to obtain the data, process, analyze and discuss the socio economic study of migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency of: 1) social interaction, 2) the level of income, 3) education, 4) housing conditions. This study considered the descriptive research. The study population was a homesteader who is in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency. Samples were taken with a random sampling technique with the proportion of 15% of the population in the study area, totaling 134 sample households. Guided data collection using questionnaires, statistical analysis used is descriptive by using a percentage formula. The results showed: 1) social interaction homesteader in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (100%) where between one and the other one to know one another. 2) the level of income migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (54%) a week on average Rp 600000-800000, 3) education level of migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (52%) had graduated from junior high school, 4) housing conditions of migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (100%) are permanent.